Mechanisms for pigmentation of Porphyromonas gingivalis and growth inhibition by yogurt-derived lactobacillus delbrueckii. - Cornacchione, Louis. (Tufts University. Tisch Library., 2019)
Porphyromonas gingivalis is an important pathogen implicated in the development of periodontitis. Cellular pigmentation is an important virulence factor of the oral pathogen P. gingivalis. We utilized a transposon mutant library of P. gingivalis strain ATCC 33277 and screened for pigmentation-defective colonies using massively parallel sequencing of the transposon junction (Tn-seq) to identify genes involved in pigmentation. Transposon insertions at 235 separate sites, located in 67 genes and 15 intergenic regions, resulted in altered pigmentation: 7 of the genes had previously been shown to be involved in pigmentation, while 75 genes and intergenic regions had not. Deletions of PGN_0361/PG_0264, a putative glycosyltransferase gene, abolish pigmentation, modulate gingipain protease activity, and alter lipopolysaccharide. Despite a growing interest in using probiotic micro-organisms to prevent disease, little is understood about the mechanisms by which probiotics exert their action. We isolated several strains of Lactobacillus delbrueckii from dairy products and examined their ability to inhibit P. gingivalis growth in vitro. We observed strain-specific inhibition of P. gingivalis growth in vitro. Whole genome sequencing of inhibitory and non-inhibitory strains of L. delbrueckii revealed significant genetic differences supporting the strain specificity of the interaction. Extracts of the STYM1 L. delbrueckii inhibitory strain contain inhibitory activity that is abolished by treatment with heat, proteinase K, catalase, and sodium sulfite. We purified the native inhibitory protein(s) from STYM1 L. delbrueckii extracts using ammonium sulfate precipitation, anion exchange chromatography, and gel filtration chromatography. Pyruvate oxidase was highly enriched in the purified samples. Addition of pyruvate oxidase substrates and cofactors to STYM1 extracts enhances the production of hydrogen peroxide. We showed that purified, catalytically-active, recombinant pyruvate oxidase is sufficient to inhibit P. gingivalis growth in vitro without the addition of cofactors. Lastly, we determined that the pyruvate oxidase from STYM1 is catalytically activated by phosphotidylethanolamine. Our results underscore the importance of strain selection, not simply species selection, in understanding microbial interactions. Specific L. delbrueckii strains or their products may be effective in the treatment and prevention of P. gingivalis-associated periodontal disease.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Linden Hu.; Committee: Andrew Camilli, Katya Heldwein, Michael Malamy, and Linc Sonenshein.; Keyword: Microbiology.